Tea Tree Oil Terpinen-4-ol Protects Gut Barrier Integrity by Upregulation of Tight Junction Proteins via the ERK1/2-Signaling Pathway - Yong, Yanhong; Fang, Biao; Huang, Yingxin; Li, Junyu; Yu, Tianyue; Wu, Lianyun; Hu, Canying; Liu, Xiaoxi; Yu, Zhichao; Ma, Xingbin; Gooneratne, Ravi; Li, Sidong; et al. (Frontiers in Nutrition, 2022)
Tea tree oil (TTO) exhibits a potent antioxidant, antibacterial, and anti-inflammatory activity and is commonly used in skincare products. However, it is not clear whether TTO can protect gut barrier damage in inflammatory bowel disease (IBD) patients. Herein, we report the impact of terpinen-4-ol (TER, the primary constituent of TTO), on lipopolysaccharide (LPS)-induced intestinal epithelial cell barrier function impairment in intestinal porcine epithelial cell lines (IPEC-J2) and dextran sulfate sodium (DSS)-induced IBD in mice. TER protected against LPS-induced damage in IPEC-J2 cells in vitro and attenuated DSS-induced colitis in vivo. Added TER promoted the tight junction (TJ) proteins expressing in vitro and in vivo and attenuated the LPS-induced upregulation of ERK phosphorylation in IPEC-J2 cells. However, when an inhibitor of ERK phosphorylation was added, TER did not promote the expression of TJ protein, denoting that the ERK signaling pathway mediates the upregulation of TJ proteins. Our data may propose the potential application of TER in treating IBD.